Distribution of autoantibodies to insulinoma‐associated antigen‐2 and zinc transporter 8 in type 1 diabetes and latent autoimmune diabetes: A nationwide, multicentre, cross‐sectional study. Issue 2 (29th November 2022) - Fan, Wenqi; Nan, Xixi; Peng, Yiman; Li, Xia; Xiang, Yufei; Yan, Xiang; Xie, Zhiguo; Zhou, Houde; Tang, Xiaohan; Cheng, Jin; Niu, Xiaohong; Liu, Jing; et al.
Abstract: Aims: This study investigated insulinoma‐associated‐2 autoantibody (IA‐2A) and zinc transporter 8 autoantibody (ZnT8A) distribution in patients with type 1 diabetes (T1D) and latent autoimmune diabetes (LAD) and the autoantibodies' association with clinical characteristics and HLA‐DR‐DQ genes. Materials and Methods: This cross‐sectional study recruited 17, 536 patients with diabetes from 46 hospitals across China. A total of 189 patients with T1D and 58 patients with LAD with IA‐2A positivity, 126 patients with T1D and 86 patients with LAD with ZnT8A positivity, and 231 patients with type 2 diabetes (T2D) were selected to evaluate islet autoantibodies, clinical phenotypes, and HLA‐DR‐DQ gene frequency. Results: IA‐2A was bimodally distributed in patients with T1D and LAD. Patients with low IA‐2A titre LAD had lower fasting C‐peptide (FCP) ( p < 0.01), lower postprandial C‐peptide (PCP) ( p < 0.001), and higher haemoglobin A1c (HbA1c) levels ( p < 0.05) than patients with T2D. Patients with high IA‐2A titre LAD were younger than patients with low IA‐2A titre LAD ( p < 0.05). Patients with low IA‐2A titre T1D had lower FCP ( p < 0.01), lower PCP ( p < 0.01), and higher HbA1c levels ( p < 0.05) than patients with high IA‐2A titre LAD. HLA‐DR‐DQ genetic analysis demonstrated that the frequency of susceptible HLA haplotypes was higher in IA‐2A‐positive patients ( p < 0.001) than in patients with T2D. Patients with high ZnT8A titre LAD had lower FCP ( p = 0.045), lower PCP ( p = 0.023), and higher HbA1c levels ( p = 0.009) and a higher frequency of total susceptible haplotypes ( p < 0.001) than patients with low ZnT8A titre LAD. Conclusions: IA‐2A in patients with T1D and LAD was bimodally distributed, and the presence of IA‐2A could demonstrate partial LAD clinical characteristics. ZnT8A titre had a certain predictive value for islet functions in patients with LAD.